Daily Mean Sea Level and Short-Period Seiches - Godin, Gabriel (The International Hydrographic Review, 2015)
Slow water-level variations and short-period seiches are found at the outer ends of the tidal spectrum. In order to isolate these types of oscillation from the body of the tide it is necessary to filter the observations. In this paper the filter theory is briefly set out first and then two simple and practical filters are discussed. The one consists of symbol products of arithmetical means and can be used to detect the true variations of the daily mean sea level. The other, which is a product of differences, isolates short-period seiches fairly well.